A comparative study between aloe vera gel dressing and conventional dressing in chronic wounds - Athavale, Virendra S.; Khandalkar, Shivmurti N.; Mahawar, Megha; Shetty, Iresh; Lad, Aditya (International Surgery Journal, 2017)
Background: The aim of this study was to evaluate the effectiveness and rate of healing of Aloe vera gel in treatment of chronic wounds, to compare the effectiveness of Aloe vera gel with conventional dressing (normal saline and povidone iodine) and to assess the percentage reduction of wound healing with Aloe vera gel dressing. Methods: The study was conducted at Dr. D. Y. Patil Medical College and Hospital, DPU University, for a period of 2 months (from January 2017 to March 2017) and is a prospective and comparative randomized type of study using 50 cases (Group A and Group B, 25 each). The study was approved by the Institute’s Ethics Committee. Results: Data analysis showed that at the end of 4 weeks, mean surface area in Group A is reduced to 4.58 cm2 from 9.79 cm2 which is higher than that in the control group. Also, the average rate of healing in Aloe vera gel is more than control group. Percentage reduction in ulcer surface area was calculated to be much more in Group A as compared to Group B. Conclusions: The study concluded that Aloe vera gel is highly effective in treatment of chronic ulcers and stimulates the growth of wound healing. Thus, reducing the hospital stay. Apart from being efficacious in wound healing, Aloe vera gel is safe product. No allergic reactions/infections were associated with Aloe vera gel. Aloe vera gel not only heals faster but is also cost effective.